PENGARUH BUDAYA KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR SEKRETARIAT DAERAH PROVINSI KALIMANTAN TIMUR - Mayang Sariyanida Pradita (ADMINISTRASI PUBLIK, 2020)
The purpose of this research is to know the magnitude of Work culture on employee performance at East Borneo district office. Type of research or explanation used is quantitative used to analyze the influence between research variables. Types of data used are kusioner, observation, interview, and documentation.of r count 0,404> r table 0,256 for 5% significance hence can be concluded that there is positive and significant influence between Work Culture with Performance of Employee at Sekretariat Daerah Provinsi East Borneo District..Office..of..East.Regency.Thus 40% of employee performance variation can be explained by Work Culture variables while the rest is explained by other variables not proposed in this research.